Trends and barriers of emergency medical service use in Addis Ababa; Ethiopia - Menbeu Sultan; Yonas Abebe; Assefu Welde Tsadik; Asmamaw Ababa; Alegnta Gebre Yesus; Nee-Kofi Mould-Millman (BMC Emergency Medicine, 2019)
Abstract Background The increasing burdens of trauma and time sensitive non-communicable disease in Addis Ababa necessitate a robust emergency medical care system. The objectives of this study were to assess the proportion of patients who used emergency medical services (EMS) and to quantitatively and qualitatively assess barriers to EMS utilization in Addis Ababa. Methods A cross-sectional quantitative and qualitative study was conducted on patients who visited five selected public hospitals in Addis Ababa with specific emergency conditions. Data were collected by trained nurses using a standardized questionnaire. Descriptive statistics and logistic regression was done on cleaned and coded quantitative data using SPSS version 20. Thematic analysis was performed on the qualitative data. Ethical approval was obtained prior to the study. Results A total of 429 participants completed the survey with a non-response rate of 5.1%. The most common emergency scene was the home (n = 222, 51.8%) followed by road side (n = 159, 37.1%). Only 87(20.3%) patients arrived by ambulance, though a majority (53.4%) of participants recalled at least one access number for an ambulance service and 96.3% stated that ambulances were an important part of the continuum of care for their emergency condition. A higher proportion of participants believed that ambulance transportation is generally safer (n = 341, 78.5%) and faster (n = 298, 69.5%) than emergency transport by taxi or private car. Patients who were non-Amharic speaking had a negative association with arriving by ambulance (P = 0.001, OR 0.47; C.I, 0.31, 0.71). The median acceptable time to get the ambulance (according to respondent’s perception) was 16 min but actually perceived ambulance waiting time was 40 min. Conclusion EMS utilization in Addis Ababa is relatively low and emergency patients are instead being transported by taxi or private car. Perceived longer ambulance waiting time and language barriers may have contributed for low utilization. Findings of this study suggest an action to improve access by improving ambulance availability while simultaneously enhancing the public’s knowledge and perception of EMS in Addis Ababa.